CD9- and CD81-positive extracellular vesicles provide a marker to monitor glioblastoma cell response to photon-based and proton-based radiotherapy - Jennrich, Sara; Pelzer, Martin; Tertel, Tobias; Koska, Benjamin; Vüllings, Melanie; Thakur, Basant Kumar; Jendrossek, Verena; Timmermann, Beate; Giebel, Bernd; Rudner, Justine (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is the most aggressive tumor of the central nervous system with a poor prognosis. In the treatment of GBM tumors, radiotherapy plays a major role. Typically, GBM tumors cannot be cured by irradiation because of intrinsic resistance mechanism. An escalation of the irradiation dose in the GBM tumor is difficult due to the high risk of severe side effects in the brain. In the last decade, the development of new irradiation techniques, including proton-based irradiation, promised new chances in the treatment of brain tumors. In contrast to conventional radiotherapy, irradiation with protons allows a dosimetrically more confined dose deposition in the tumor while better sparing the normal tissue surrounding the tumor. A systematic comparison of both irradiation techniques on glioblastoma cells has not been performed so far. Despite the improvements in radiotherapy, it remains challenging to predict the therapeutical response of GBM tumors. Recent publications suggest extracellular vesicles (EVs) as promising markers predicting tumor response. Being part of an ancient intercellular communication system, virtually all cells release specifically composed EVs. The assembly of EVs varies between cell types and depends on environmental parameters. Here, we compared the impact of photon-based with proton-based radiotherapy on cell viability and phenotype of four different glioblastoma cell lines. Furthermore, we characterized EVs released by different glioblastoma cells and correlate released EVs with the cellular response to radiotherapy. Our results demonstrated that glioblastoma cells reacted more sensitive to irradiation with protons than photons, while radiation-induced cell death 72 h after single dose irradiation was independent of the irradiation modality. Moreover, we detected CD9+ and CD81+ EVs in the supernatant of all glioblastoma cells, although at different concentrations. The amount of released CD9- and CD81-positive EVs increased after irradiation when cells became apoptotic. Although secreted EVs of non-irradiated cells were not predictive for radiosensitivity, their increased EV release after irradiation correlated with the cytotoxic response to radiotherapy 72 h after irradiation. Thus, our data suggest a novel application of EVs in the surveillance of anti-cancer therapies.